Determining the Beginning of Ramadan in Malaysia: Balancing Tradition, Astronomy, and Religious Principle - Mohd Abid Mohd Azhar; Mohd Nawawi, Mohd Saiful Anwar; Nurulhuda Ahmad Zaki; Muhamad Syazwan Faid; Muhammad Ridzuan Hashim (Advances in Humanities and Contemporary Studies, 2025)
This paper explores the process of determining the beginning of Ramadan in Malaysia, focusing on the integration of Islamic legal principles, traditional practices, and advances in astronomical science. It highlights the use of hisab rukyah, which combines astronomical calculations and physical moon sighting, ensuring that official decisions are both scientifically accurate and religiously valid. The paper examines the historical use of the MABIMS criteria, first introduced in 1995 and revised in 2021, and evaluates their effectiveness in improving the reliability of crescent sighting decisions. Using a mixed methodology—including data analysis, astronomical simulations, criteria comparisons, and field observations—the study identifies the strengths and challenges of Malaysia’s current approach. It also compares the MABIMS criteria with international standards and emphasizes the need to address emerging issues such as telescopic observation and light pollution. Finally, the paper offers future recommendations, including the recognition of telescopic data, the development of more dynamic crescent visibility criteria, and enhanced public education efforts. These steps aim to strengthen Malaysia’s position as a regional leader in Islamic astronomy and to promote unity within the Muslim community